A method of producing biodiesel heterogeneous catalytic system - Yap, Taufiq Yun Hin (2011)
A method of producing a mixture of methyl ester from an oil source comprises the step of reacting the oil source with an alcohol in the presence of a heterogenous catalytic system derived from mixed metal oxide of calcium and a second metal.